AVIATION LEASING AGREEMENTS AS FINANCIAL PROPELLER FOR THE NEWCOMERS - Luca Leone (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
It is possible nowadays to verify the efficacy of various aviation leasing agreements that have been in use during the last forty years. Hereafter the paper presents the most common of them, highlighting their role as propellers of a new financial strategy in the aviation market.